Form of worshiping Jyeshtha Gauri - Mumbai Archive Project Team (Jio Institute, 2024)
In coastal Maharashtra, Jyeshtha Gauri is typically worshipped as a metal facemask attached to an anthropomorphic body adorned with traditional Koli attire and jewellery. A Nauvari saree, a type of saree worn by Koli women, is offered to the Goddess and changed every year.